Achieving partial denitrification-anammox in biofilter for advanced wastewater treatment. (May 2020) - Cui, Bin; Yang, Qing; Liu, Xiuhong; Wu, Wenjun; Liu, Zhibin; Gu, Pengchao
Graphical abstract: Highlights: Advanced wastewater treatment was achieved in PDN-Anammox biofilter. Nitrification and partial denitrification both occurred to PDN biofilter. Nitrite accumulation ratio reached to 75.4% with low abundances of nirK and nirS . Anammox biofilter was stable and contributed to 74.6% of nitrogen removal. Ca. Brocadid fulgida gradually became dominant bacteria in Anammox biofilter. Abstract: Recently, partial denitrification (PDN) - anaerobic ammonium oxidation (anammox) process has been widely studied in activated sludge for nitrate wastewater treatment. However, achieving PDN-Anammox in biofilter for domestic wastewater treatment was never reported. In this study, two lab-scale PDN biofilter and Anammox biofilter were built up to treat simulated domestic wastewater. The results showed that stable nitrogen removal performance was kept with averaged effluent nitrogen of 10.2 mg/L. Stable nitrite accumulation performance was achieved with low abundance of nitrite reductase gene, while influent composition influenced nitrogen transformation pathway in PDN biofilter. When treating domestic wastewater, nitrification and partial denitrification led to the higher nitrite accumulation ratio of 75.4%. The percentage contribution of anammox biofilter was 74.6% for nitrogen removal, and Candidatus Brocadia was dominant genus. After long-term operation, limited substrate concentration caused interspecific competition among various anammox bacteria, leading to an increasing proportion of Candidatus Brocadia fulgida . PDN-Anammox biofilter is a feasible process to advanced wastewater treatment, which could save aeration consumption and carbon source addition, and reduce sludge production.